Relating to the Speaker behind the Voice: What Is Changing? - Deamer, Felicity; Hayward, Mark (Frontiers in Psychology, 2018)
We introduce therapeutic techniques that encourage voice hearers to view their voices as coming from intentional agents whose behavior may be dependent on how the voice hearer relates to and interacts with them. We suggest that this approach is effective because the communicative aspect of voice hearing might fruitfully be seen as explanatorily primitive, meaning that the agentive aspect, the auditory properties, and the intended meaning (interpretation) are all necessary parts of the experience, which contribute to the impact the experience has on the voice hearer. We examine the experiences of a patient who received Relating Therapy, and explore the kinds of changes that can result from this therapeutic approach.